Lectinas de Canavalia brasiliensis Mart.: comportamento durante a maturação da semente - Silva, Lia Magalhães de Almeida (1986)
The behavior of the lectin and other protein from Canavalia brasiliensis Mart. seed was investigated during the maturation process. The Canavalia brasiliensis flowers appeared 150 days after germination. The pods were collected in 5 days intervals until complete maturation and separated in three parts:pericarp, seed coat and cotyledons + axis. The lectin was found only in cotyledons during maturation [...]